Solubility determination and thermodynamic modelling of 5-chloro-8-hydroxyquinoline in binary solvent mixtures from T = 278.15 to 323.15 K. (March 2021) - He, Haixia; Sun, Renren; Wan, Yameng; Jiang, Gaoliang; Sha, Jiao; Li, Yu; Li, Tao; Ren, Baozeng
Highlights: Solubility of cloxiquine (Form Ⅰ) in three binary solvents was determined. Four thermodynamic models were used to correlate the experimental solubility. Solubility depended strongly on the temperature and solvent composition. The mixing and dissolution thermodynamics of cloxiquine were calculated by UNIQUAC model. Abstract: The equilibrium solubility of 5-chloro-8-hydroxyquinoline [cloxiquine] (Form Ⅰ) from 278.15 to 323.15 K in three binary solvent systems [(2-ethoxyethanol, n -propyl acetate and 1, 4-dioxane) + ethanol] was measured by using laser monitoring method. The obtained results indicated that the solubility of cloxiquine was found to increase monotonically with the augmented of system temperatures and mass fraction of (2-ethoxyethanol, 1, 4-dioxane or n -propyl acetate) in binary solvent mixtures. Moreover, experimental cloxiquine solubility was adequately correlated with the three-suffix Margules model, NRTL model, Wilson model and UNQUAC model, with the best fitting from the UNIQUAC model. Furthermore, the thermodynamic parameters (entropy, Gibbs energy and enthalpy changes) of mixing and dissolution processes were computed from the accurate solubility data using the UNIQUAC model. In this context, the relevant analysis about positive entropy change and negative Gibbs energy change indicated that the whole dissolution process was confirmed to entropy-driving and spontaneous.